Salt appetite: interaction of forebrain angiotensinergic and hindbrain serotonergic mechanisms - Menani, José Vanderlei [UNESP]; Colombari, DSA; Beltz, T. G.; Thunhorst, R. L.; Johnson, A. K. (Elsevier B.V., 1998)
Methysergide injected bilaterally into the lateral parabrachial nucleus (LPBN) increases NaCl intake in several models of renin-dependent salt appetite. The present study investigated the role of angiotensin Type 1 (AT(1)) receptors in the subfornical organ (SFO) on this effect. The intake of 0.3 M NaCl and water was induced by combined administration of the diuretic, furosemide (FURO), and the angiotensin-converting enzyme inhibitor, captopril (CAP). Pretreatment of the SFO with an AT, receptor antagonist, losartan (1 mu g/200 nl), reduced water intake but not 0.3 M NaCl intake induced by subcutaneous FURO + CAP. Methysergide (4 mu g/200 nl) injected bilaterally into the LPBN increased 0.3 M NaC1 intake after FURO + CAP. Losartan injected into the SFO prevented the additional 0.3 M NaC1 intake caused by LPBN methysergide injections. These results indicate that AT, receptors located in the SFO may have a role in mediating an enhanced sodium intake produced by methysergide treatment. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: forebrain angiotensinergic mechanism; hindbrain serotonergic mechanisms; losartan